The Napo Runa of Amazonian Ecuador - Uzendoski, Michael, 1968- (Book collections on Project MUSE., 2005)
Based upon historical and archival research, as well as the author's years of fieldwork in indigenous communities, Michael Uzendoski's theoretically informed work analyzes value from the perspective of the Napo Runa people of the Amazonian Ecuador. _x000B_Written in a clear and readable style, The Napo Runa of Amazonian Ecuador presents theoretical issues of value, poetics, and kinship as linked to the author's intersubjective experiences in Napo Runa culture. Drawing on insights from the theory of gift and value, Uzendoski argues that Napo Runa culture personifies value by transforming things into people through a process of subordinating them to human relationships. While many traditional exchange models treat the production of things as inconsequential, the Napo Runa understand production to involve a relationship with natural beings (plants, animals, spirits of the forest), which are considered to be subjects that share spiritual substance, or samai. Throughout the book, value is revealed as the outcome of a complicated poetics of transformation by which things and persons are woven into kinship forms that define daily social and ritual life. _x000B_